The effect of common cold massage therapy on symptom improvement in children aged 3–60 months at Jatiroto Primary Health Center - Ratna Ayu Aziroh; Rosyidah Alfitri (PT WIM Solusi Prima, 2026)
Common cold is a frequent viral infection of the upper respiratory tract in infants and children under five years old. Pharmacological treatments often carry risks of side effects, shifting clinical focus toward non-pharmacological therapies such as pediatric massage. This study aims to determine the effect of common cold massage therapy on accelerating symptom improvement in children aged 3-60 months at the Jatiroto Public Health Center. A quasi-experimental pre-test and post-test design was applied to 30 respondents selected through purposive sampling. Data collected included age, gender, symptom duration, and pre-test post-test symptom scores evaluated using standard measurement scales. The data was quantitatively processed and statistically evaluated using the paired t-Test. The results showed that the mean score of common cold symptoms before therapy was 8.97, which significantly decreased to 3.97 after therapy. Bivariate analysis using a paired t-Test revealed a highly significant improvement with t = 13.935 and p < 0.001 (p = 2.21 x 10-14). It is concluded that pediatric common cold massage therapy is highly effective in reducing upper respiratory tract infection symptoms in children. This non-pharmacological approach can be implemented as a safe alternative or complementary treatment within midwifery care models in Primary Health centers.